Lenvatinib Therapy in Patients with Unresectable Hepatocellular Carcinoma in Real Clinical Practice - V. V. Petkau; A. V. Sultanbaev; K. V. Menshikov; A. S. Antipin; M. V. Volkonsky; V. M. Filippova; Yu. V. Vasilyeva; A. A. Tarkhanov; M. R. Mukhitova; M. Zh. Murzalina; A. R. Safarova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To determine lenvatinib treatment outcomes in patients with advanced unresectable hepatocellular carcinoma (uHCC) in real clinical practice.Patients and methods. A multicenter retrospective observational study included 58 patients with a confirmed uHCC diagnosis receiving lenvatinib. At baseline, ECOG, Child-Pugh and BCLC scores were assessed. The objective response rate (ORR), disease control rate (DCR), median overall survival (OS) and median progression-free survival (PFS) rates were assessed. In addition, adverse effects (AE) during treatment were monitored.Results. The median OS and PFS comprised 14.6 (95 % CI 10.6–18.6) and 11.1 months (95 % CI 8.31–13.8), respectively. The ORR amounted to 32.8 %, while DCR reached the level of 79.3 %. The levels of ORR and DCR were not statistically significantly different between the patients with stages B and C according to the BCLC staging system, with grades 0 and 1 according to ECOG, with classes A and B according to the Child-Pugh score, with viral and non-viral HCC etiology, with and without extrahepatic spread, and with and without portal vein invasion. Patients with alpha-fetoprotein (AFP) blood levels <200 ng/mL showed significantly higher ORR and DCR compared to those with AFP levels >200 ng/mL (44.4 % vs. 13.6 %, p = 0.015; and 88.9 % vs. 63.6 %, p = 0.021, respectively). The uHCC stage according to BCLC, ECOG functional status, Child-Pugh class, presence or absence of extrahepatic spread and viral etiology had no effect on the OS and PFS median levels. Patients with macroscopic portal vein invasion had a significantly lower PFS compared with those lacking this complication: 3.97 (0.00-8.07) vs. 11.1 (8.46-13.7), p = 0.053. AFP levels ≥200 ng/mL adversely affected survival rates: median OS comprised 12.0 (5.95-18.9) months in the group of patients with AFP ≥200 ng/mL vs. 16.1 (8.73-23.5) months in the group of patients having AFP <200 ng/mL, p = 0.020. AEs were registered in 81.0% (n = 47) of patients. Among the most common AEs were arterial hypertension (32.8 %), weakness (24.1 %), weight loss (12.1 %) and appetite loss (10.3 %). Due to AEs, Lenvatinib was withdrawn in 5 (8.6 %) patients.Conclusion. Lenvatinib confirmed its efficacy and safety in patients with uHCC in real clinical practice. The treatment outcome might be affected by AFP levels and the presence of macroscopic portal vein invasion. Further comparative studies into treatment regimens applied in real clinical practice are required.